PENERAPAN TPACK DALAM PENGEMBANGAN MICROSITES UNTUK PEMBELAJARAN IPS ANAK TK ‘AISYIYAAH BUSTANUL ATHFAL 1 DI ERA DIGITALISASI - Susilowati, Dian; Andriana; Yatimah, Sri; Sudarmiani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was conducted to address the low level of social skills and learning activeness of Group B students at TK ’Aisyiyah Bustanul Athfal 1 Madiun City, which in the preliminary research only reached 48.6% and 46.3% in the “very well developed” category. As a solution, teachers developed a learning medium based on Microsites containing games, materials, and stories with simple animated displays that can be accessed through an Interactive Flat Panel. The results of the study showed that the use of Microsites was able to improve social skills, such as peer interaction, environmental awareness, and empathy in learning, as well as enhance learning activeness through focus, participation, and initiative. The percentage of social skills increased to 81.1% and learning activeness to 80.9%, proving that Microsites are effective as an innovative learning medium in the digitalization era.